1991
DOI: 10.1172/jci115213
|View full text |Cite
|
Sign up to set email alerts
|

1,25-dihydroxyvitamin D3 modulates growth of vascular smooth muscle cells.

Abstract: We examined the effects of 1,25-dihydroxyvitamin D3(1,25-(OH)2D3) on the proliferation of vascular smooth muscle (VSM) cells. Receptors for 1,250-H)2D3 were demonstrated in fresh rabbit aortic tissue and in cultured rat VSM using binding of 13H1-1,25-0H)2D3 in sucrose density gradients of the tissue or cell homogenates. The receptor sedimented at 3.6 S, the sedimentation velocity of 1,2501H)2D3 receptors from other sources. 1,2540H)2D3 dramatically altered the growth of VSM, but this effect depended importantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
95
1
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(101 citation statements)
references
References 37 publications
3
95
1
2
Order By: Relevance
“…VDR s which are DNA-linked proteins (Mitsuhashi et al 1991) were identified in SMCs in vitro (Kawashima 1987, Merke et al1987, Koh et al 1988. Stimulation of these receptors induce cell proliferation and differentiation in several tissues (Pike 1985, Pols et al 1990, Walters 1992, and there is an increase in DNA synthesis and a decrease in heparan sulfate, a glycosaminoglycan responsible for the inhibition of the proliferation of these cells, allowing multiplication of the SMCs (Koh et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…VDR s which are DNA-linked proteins (Mitsuhashi et al 1991) were identified in SMCs in vitro (Kawashima 1987, Merke et al1987, Koh et al 1988. Stimulation of these receptors induce cell proliferation and differentiation in several tissues (Pike 1985, Pols et al 1990, Walters 1992, and there is an increase in DNA synthesis and a decrease in heparan sulfate, a glycosaminoglycan responsible for the inhibition of the proliferation of these cells, allowing multiplication of the SMCs (Koh et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D exerts its action at a cellular level through binding of the active metabolite 1,25-dihydroxyvitamin D to the vitamin D receptor (VDR). The VDR is expressed in many different cell types such as pancreatic b cells (1), vascular smooth muscle cells (2), and osteoblasts and chondrocytes (3). Several polymorphisms in the gene encoding the VDR, such as Cdx2, FokI, BsmI, ApaI, and TaqI, have been demonstrated to be related to bone characteristics and risk of fractures, although results remain equivocal (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Both endothelial cells and vascular smooth muscle cells (VSMCs) express high-affinity receptors for 1,25(OH) 2 vitamin D 3 , 1,2 and vitamin D metabolites exert numerous effects in VSMCs [3][4][5][6][7][8][9][10] that involve vital aspects of VSMC function and pathology, including contractility, growth and migration, and the evolution of vascular calcifications. Vitamin D metabolites appear to enhance the expression of Ca-ATPase, 3 increase the entry of calcium into the cell, 4 raise cytosolic free calcium, 5 induce the expression of contractile proteins, 6 and accelerate the formation of prostacyclin 7 in VSMCs, all of which may directly or indirectly affect arterial tone.…”
mentioning
confidence: 99%
“…Vitamin D metabolites appear to enhance the expression of Ca-ATPase, 3 increase the entry of calcium into the cell, 4 raise cytosolic free calcium, 5 induce the expression of contractile proteins, 6 and accelerate the formation of prostacyclin 7 in VSMCs, all of which may directly or indirectly affect arterial tone. Evidence also suggests that 1,25(OH) 2 vitamin D 3 inhibits VSMC replication 8,9 and diminishes the mitogenic response to growth enhancers such as thrombin or platelet-derived growth factor (PDGF). 9 On the other hand, 1,25(OH) 2 vitamin D 3 may accelerate cell migration 10 and promote the transition of contractile VSMCs into a secretory cell phenotype.…”
mentioning
confidence: 99%
See 1 more Smart Citation